Perancangan Sistem Pelaporan Tanam Dan Hasil Pertanian Di Wilayah Kabupaten Bandung Barat Berbasis Web - Yulianus Palopak; Erlangga Zulfikar (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2017)
In the current era of globalization, information technology has become one of the important aspects to support the work carried out in every field that exists. Parongpong is one of the sub-districts in West Bandung Regency which has a fairly extensive agricultural fields. The reporting system for cropping and harvesting results is a web application that has an important role to interact with farmers in the area around the agricultural area under the auspices of the Regional Agricultural Service or the Regional Government. To help farmers determine the commodities to be planted on their available land and realize the current market price stability. The purpose of this study is 1) Can provide information on what commodities should be planted by farmers in the West Bandung Regency. 2) Can help the Regional Government of West Bandung Regency and farmers to equalize the planting of a commodity. 3) Can help the Regional Government of West Bandung Regency to do equal distribution of prices from the yield of a commodity. Information system application design methods the author uses the SDLC (System Development Life Cycle) method. From the results, the authors can draw conclusions are 1) The Agricultural Service Information System designed only includes data collection of reports inputted by farmers, and the admin can only retrieve data in accordance with what is displayed. 2) This Information System can help Farmers to know statistics and price predictions going forward. 3) Information systems built can store data that is in accordance with what is desired. 4) With this Information System, the Agriculture Service will simplify work in monitoring farmers and recording existing data. The suggestions given from the author are 1) The website address or url link is only known by certain parties or using the official site. 2) There is information on the quota for planting a crop, in a location from the West Bandung District Agriculture Service.